Exploring undergraduates’ money-management life insight from an emerging economy - Sachitra, Vilani; Wijesinghe, Dinushi; Gunasena, Wajira (Emerald Publishing Limited, 2019)
Attached
Keywords: Qualitative approach, Undergraduates, Beyond financial literacy, Money-management behaviour